MEDIATISASI PADA AKTIVITAS DAKWAH PEREMPUAN SALAFI - Prima Ayu Mahanani (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
Technology has big impact for our interaction in social-cultural life. It also happens at Dakwah by woman Salafi which mediate by WhatsApp application. This paper attempts to explain deeply about mediatisasi by Woman Salafi in their activies. The aim of this paper is to break the stronger the dominance of media logic in religion. The concept of this research refer to mediatisasi concept develop by StigHjarvard at institution stages. This research use qualitative approach by using interview method focus in two informan who have chosen based on specific criteria. In this research, the writer use ethnography analysis to analyze the data and dialogic validity analysis to analyze the data validity. The result of the research shows that there is cultural changing in dakwah activity by Woman Salafi. Mediatisasi in dakwah activity by Woman Salafi shows that religion has movement in media. Media has become an integral part of Woman Salafi and also as a big structure in ManhajSalafi.